Sosialisasi Pola Asuh Efektif dan Harmonis untuk Mencegah Kenakalan Remaja - Satino Satino; Yuliana Yuli Wahyuningsih; Atik Winanti; Marina Ery Setyawati; Iwan Erar Joesoef (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Juvenile delinquency is a social phenomenon that often occurs during the transition from childhood to adulthood. Adolescence is known as a phase of identity discovery that is vulnerable to the influence of various external and internal factors. One of the main factors influencing adolescents' tendency to engage in deviant behavior is the family environment. The family plays a crucial role as the first social environment that provides values, norms, and controls for children's behavioral development. This study aims to determine the extent of family influence, particularly parenting styles, communication quality, and family unity, on the emergence of juvenile delinquency. The research method used is a descriptive qualitative approach with data collection techniques through literature review and in-depth interviews with several adolescents and their parents. Data were analyzed to identify the relationship between parenting styles and family dynamics with adolescent behavior. The results show that families with disharmony, minimal communication, and overly authoritarian or permissive parenting styles have a higher tendency to produce deviant behavior in children. Adolescents from such families are more vulnerable to negative associations, social pressure, and have difficulty controlling their emotions. Conversely, families that implement democratic parenting styles, provide emotional attention, and foster open communication tend to foster more emotionally, socially, and morally stable adolescents. This research confirms that strengthening the family's role is key to preventing juvenile delinquency. This can be achieved through improving the quality of communication between family members, implementing parenting styles that balance control and freedom, and maintaining harmony within the household. In this way, the family can function optimally as the first line of defense in shaping positive adolescent character and behavior, thereby minimizing the risk of delinquency.